Effectiveness of Developmental Care in Reducing Physiological Stress among Low-Birth Weight Infants - Siti Nurhayimah; Trisna Vitaliati (Journal of Nursing Periodic, 2026)
Introduction: Infants with low birth weight (LBW) are at high risk of experiencing physiological stress due to immaturity of organ systems and exposure to neonatal intensive care environments. Physiological stress can affect the stability of vital signs, sleep quality, and the baby's growth and development process. Developmental care is a treatment approach that focuses on providing stimulation according to the baby's developmental needs to minimize stress and increase physiological stability. This study aims to analyze the effectiveness of developmental care in reducing physiological stress in babies with low birth weight. Methods: This study uses a pre-experiment design. The research population is LBW babies who are in the Perinatology room of dr. Soebandi Jember Hospital. The number of samples in this study was 37 LBW babies who were selected using the non-probability sampling technique using the purposive sampling method. The independent variable of the study is the application of Developmental Care in the form of an incubator cover. Meanwhile, the dependent variable is the baby's physiological stress level, which is assessed based on the baby's vital signs before and after the intervention. The research measurement tool was taken using a physiological scale observation sheet, which consisted of 4 indicators, namely HR, RR, SpO₂, and body temperature. Statistical analysis was carried out by means of the Friedman Test to find out the difference in the score of each indicator from day 1 to day 3 and the Kruskal-Wallis Test (non-parametric Anova) to find out the difference in total physiological stress scores between days. Results: There was a significant decrease in the average score of Heart Rate (HR), Respiratory Rate (RR), SpO₂, and Body Temperature from day 1 to day 3 (p = 0.000 for each indicator). The total physiological stress score also showed a decrease from an average of 84.55 to 40.00 (p = 0.000). Conclusions: Developmental care is effective in reducing physiological stress in babies with low birth weight. This approach can be applied as one of the neonatal nursing strategies to improve comfort, physiological stability, and support the growth and development process of LBW babies.